Some Remarks on the Restriction Theorems for the Maximal Operators on $\mathbb{R}^d$ (Analysis in Theory and Applications, 2017)
The aim of this paper is to give a simple proof of the restriction theorem for the maximal operators on the $d$-dimensional Euclidean space $\mathbb{R}^d$, whose theorem was proved by Carro-Rodriguez in 2012. Moreover, we shall give some remarks of the restriction theorem for the linear and the multilinear operators by Carro-Rodriguez and Rodriguez, too.
Keywords: Weighted $L^p$ spaces; Fourier multipliers; multilinear operators.